2019
DOI: 10.4196/kjpp.2019.23.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Orai1 in tunicamycin-induced endothelial dysfunction

Abstract: Endoplasmic reticulum (ER) stress is mediated by disturbance of Ca 2+ homeostasis. The store-operated calcium (SOC) channel is the primary Ca 2+ channel in non-excitable cells, but its participation in agent-induced ER stress is not clear. In this study, the effects of tunicamycin on Ca 2+ influx in human umbilical vein endothelial cells (HUVECs) were observed with the fluorescent probe Fluo-4 AM. The effect of tunicamycin on the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…As a non-excitable cell, there are two types of Ca2+ channels, L-type channels (Cav1.2) and SOC channels which are the majority; the rare is Cav1.2. A previous study found that Orai1-mediated Ca 2+ influx decreased endothelial nitric oxide synthase (eNOS) expression induced by tunicamycin, which attributes to endothelial dysfunction [ 21 ]. This is consistent with our finding that Orai1 and TRPC1 regulated Ca 2+ entry contribute to endothelial apoptosis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a non-excitable cell, there are two types of Ca2+ channels, L-type channels (Cav1.2) and SOC channels which are the majority; the rare is Cav1.2. A previous study found that Orai1-mediated Ca 2+ influx decreased endothelial nitric oxide synthase (eNOS) expression induced by tunicamycin, which attributes to endothelial dysfunction [ 21 ]. This is consistent with our finding that Orai1 and TRPC1 regulated Ca 2+ entry contribute to endothelial apoptosis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, high glucose induced the up-regulation of Ora1-3 proteins and enhanced SOCE activity in human coronary artery endothelial cells (HCAECs), thereby inducing endothelial hyperpermeability and hyperproliferation [ 180 ]. In agreement with these observations, the genetic silencing of STIM1 and Orai1 alleviated the increase in permeability induced by the pro-inflammatory mediator, High-Mobility Group Box 1 protein (HMGB1), in Ea.hy926 monolayers [ 181 ], whereas a selective siOrai1 alleviated tunicamycin-induced ER stress and unfolded protein response, which are a feature of atherosclerosis, were shown to be alleviated by a selective siOrai1 in HUVECs [ 182 ]. Thus, the mechanisms by which chronic inflammation or hyperglycaemia lead to atherosclerosis involve an increase in endothelial permeability and proliferation that depend on STIM1 and Orai1 ( Table 4 ) [ 183 ].…”
Section: The Endothelial I Crac Is Mediated By Sti...mentioning
confidence: 80%
“…In a study by Wen et al [ 40 ], they stimulated mammary epithelial cell line, MCF-7 cells, for 24 h with tunicamycin at four different concentrations (0, 0.1, 0.5, and 1 µg/mL), finding that tunicamycin concentrations of 0.5 and 1 µg/mL significantly increased the expression of GRP-78 and caused ER stress, and they finally selected 1 µg/mL tunicamycin to build ER stress model for their follow-up experiment. Similarly, Yang et al [ 41 ]. treated human umbilical vein endothelial cells for 24 h with tunicamycin at five different concentrations (0, 0.25, 0.5, 1, and 2 µg/mL), finding that all concentrations (except concentration = 0) of tunicamycin significantly increased the expression of GRP-78 and caused ER stress, and the expression of GRP-78 was not a significant difference among the three concentrations (0.5, 1, and 2 µg/mL).…”
Section: Discussionmentioning
confidence: 94%